PROTOTYPE SISTEM PEMANTAU KUALITAS UDARA BERBASIS RASPBERRY PI - zulhelman (Spektral, 2021)
Particulate Matter is an air pollutant substance that surrounds humans both indoors and outdoors. Humans cannot see or know the levels of pollution particles in the air and air quality without tools. Therefore, a prototype "Raspberry Pi-Based Air Quality Monitoring System" was made. This system consists of a tool, which can determine the level of pollution in the air, especially PM 2.5 and PM 10 and to detect the surrounding environmental conditions such as temperature, humidity, and air pressure, several sensors are needed. For the detection of PM 2.5 and PM 10 the PMS5003 sensor is used and for the detection of environmental conditions using the SHTC3 (air temperature and humidity) and LPS22HB (air pressure) sensors which are available in the Sense Hat B module. For the reading process using a Raspberry Pi programmed using Python and data will be processed into an Air Quality Index based on the “Polutant Standards Index”. In this study, the input specifications were tested. In the input specification test, there is a match between the Air Quality Index trend based on the location and time of data collection